Eksistensi Kesenian Rinding Gumbeng di Era Globalisasi - Nabilah Al Hafidhoh; Yuhastina Yuhastina; Yosafat Hermawan Trinugraha (Mahesa Research Center, 2022)
Research on Rinding Gumbeng art in Duren Hamlet, Beji aims to explore how the existence of Rinding Gumbeng Art in the current Globalization Era. The method used is qualitative research. Qualitative data obtained through field observations with purposive sampling technique. Qualitative data were obtained through in-depth interviews with 10 prospective participants. Qualitative data were analyzed using Spradley's domain model, which gives a general and comprehensive picture of the research object. The data obtained through surveys and interviews were then converted into a script in order to obtain an overview of the object under study. The research concludes that the existence of Rinding Gumbeng art in Dusun Duren is still growing and surviving well by undergoing changes to follow the conditions in the current era of globalization. Rinding Gumbeng art is still being preserved to this day and has even begun to be known outside the region.